2018
DOI: 10.1111/jfpp.13633
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound in orange sweet potato juice: Bioactive compounds, antioxidant activity, and enzymatic inactivation

Abstract: Orange flesh sweet potato contains bioactive compounds which have nutritional and health‐protective values. The aim of this investigation was to evaluate the impact of ultrasound treatment in orange sweet potato juice on physicochemical parameters, β‐carotene, total phenolic, antioxidant activity (ORAC and ferric thiocyanate), polyphenol oxidase, and peroxidase activity. The juice was sonicated for 2, 4, 6, 8, and 10 min, with ultrasonic intensity of 0.24 and 0.66 W cm−2. The sonicated juice showed an increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The antioxidant activity was mainly attributed to non-phenolic compounds, such as β-carotene, but also to the phenolic compounds present in the juice. In a previous study, Rios-Romero et al. (2018) reported the same tendency in sweet potato juice sonicated under different conditions.…”
Section: Resultsmentioning
confidence: 60%
See 3 more Smart Citations
“…The antioxidant activity was mainly attributed to non-phenolic compounds, such as β-carotene, but also to the phenolic compounds present in the juice. In a previous study, Rios-Romero et al. (2018) reported the same tendency in sweet potato juice sonicated under different conditions.…”
Section: Resultsmentioning
confidence: 60%
“…México). The resulting juice immediately was processed and subjected to three types of treatment: (i) ultrasound waves, applied with an ultrasonic device (UP200Ht; Hielscher Ultrasound Technology, Germany) attached to 40 mm diameter probe (treatment time of 8 min, ultrasonic intensity of 0.66 W cm −2 , and a constant frequency of 26 kHz) ( Ríos-Romero et al., 2018 ); (ii) steam treatment, performed using a domestic steamer for 2 min; (iii) a combination of steam and ultrasound treatment. A sample of juice without treatment was physicochemically characterized and used as a control.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Huang et al () reported a polyethylene glycol‐based ultrasonic‐assisted extraction of anthocyanins and phenolics from purple sweet potato. Overall, the total phenolic compounds improvement extracted from potato peels, potato flesh or discarded potatoes using ultrasound assistance was reported for several authors (Samarin et al , ; Cai et al , ; Rios‐Romero et al , ).…”
Section: Extraction Technologiesmentioning
confidence: 84%